True Lies Worldwide : Fictionality in Global Contexts. - Cullhed, Anders, 1951- (De Gruyter, 2014)
In today's world, fiction seems to be present everywhere, not only in traditional media such as books or movies, but on the web, in computer games or virtual environments. This book gathers twenty-three scholars from ten countries with the aim to explore the idea and the use of fiction in different cultures. It covers a broad field of interests, from classical literature, artand philosophy to modern media.